2004
DOI: 10.1097/01.nmd.0000126706.53615.7b
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior and Mild Traumatic Brain Injury in Major Depression

Abstract: Traumatic brain injury (TBI) is associated with psychiatric illness, suicidal ideation, suicide attempts, and completed suicide. We investigated the relationship between mild TBI and other risk factors for suicidal behavior in major depressive episode. We hypothesized that mild TBI would be associated with suicidal behavior at least partly because of shared risk factors that contribute to the diathesis for suicidal acts. Depressed patients (N = 325) presenting for treatment were evaluated for psychopathology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 32 publications
0
56
0
1
Order By: Relevance
“…TBI may act as a stressor, precipitating psychiatric illness and suicidal behaviour [7]. TBI may also act as a diathesis via disinhibition and impulsivity from frontal lobe injury [7] or through other neuropathological mechanisms.…”
Section: Tbi and Suicidementioning
confidence: 99%
“…TBI may act as a stressor, precipitating psychiatric illness and suicidal behaviour [7]. TBI may also act as a diathesis via disinhibition and impulsivity from frontal lobe injury [7] or through other neuropathological mechanisms.…”
Section: Tbi and Suicidementioning
confidence: 99%
“…Research proposed individuals with higher impulsivity being at higher risk of suicide attempts (Beautrais et al 1999;Brezo et al 2006;Oquendo et al 2004). Impulsivity in many studies was evaluated by self-report measures, and behavioral laboratory measures of impulsivity also predicted suicide attempts behavior (Dougherty et al 2004;Swann et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 650 TBI patients, five individuals had completed suicide (Harris & Barraclough, 1997), which puts the rate of suicide among this population at approximately three times the United States national average. Oquendo et al (2004) studied 325 patients who fit criteria for either Major Depressive Disorder or Bipolar I Disorder; 109 of them had experienced a mTBI (Oquendo, 2004). They found that the patients with mTBI were much more likely to attempt suicide than the patients with no history of mTBI.…”
Section: Suicidalitymentioning
confidence: 99%